Flexible CO2 Sensor Architecture with Selective Nitrogen Functionalities by One‐Step Laser‐Induced Conversion of Versatile Organic Ink. (9th October 2022) - Wang, Huize; Ogolla, Charles Otieno; Panchal, Gyanendra; Hepp, Marco; Delacroix, Simon; Cruz, Daniel; Kojda, Danny; Ciston, Jim; Ophus, Colin; Knop‐Gericke, Axel; Habicht, Klaus; Butz, Benjamin; et al.
Abstract: Nitrogen‐containing carbons (NC) are a class of sustainable materials for selective CO2 adsorption. A versatile concept is introduced to fabricate flexible NC‐based sensor architectures for room‐temperature sensing of CO2 in a one‐step laser conversion of primary films cast from abundant precursors. By the unidirectional energy impact in conjunction with depth‐dependent attenuation of the laser beam, a layered sensor heterostructure with a porous transducer and active sensor layer is formed. Comprehensive microscopic and spectroscopic cross‐sectional analyses confirm the preservation of the high content of imidazolic nitrogen in the sensor. The performance is optimized in terms of material morphology, chemical composition, and surface chemistry to achieve a linear relative resistive response of up to Δ R / R 0  = −14.3% (10% of CO2 ). Thermodynamic analysis yields Δads H values of −35.6 and 34.1 kJ·mol −1 for H2 O and CO2, respectively. The sensor is operable even in humid environments (e.g., ∆ R / R 0, RH = 80%  = 0.53%) and shows good performance upon strong mechanical deformation. Abstract : A new concept for flexible CO2 sensors with an "inverted sensor architecture" is developed based on abundant materials and simple fabrication. The sensor consists of a porous graphitic carbon layer as a conductive transducer and nitrogen‐containing carbon as a sensor layer underneath.